(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses some problems observed in the teaching process in school education, such as students’ inattentiveness and inability to concentrate, along with the factors causing these issues. It also examines methods recommended for teachers to overcome these challenges. The challenges observed during the teaching practice process in schools and the methods to solve them were highlighted in this article.